Research On Life Long Learning - Hassan, Hasahudin; T., Senthil Kumar; Mohammad, Aslam (The International Journal Research Publication, 2018)
Lifelong Learning (LLL) has been attributed to various benefit. This study intends to give a clear concept of the definition of LLL, together with summary of its top advantages and finally its practical application to University Malaysia Pahang (UMP). By definition, it means diversifiable, adaptable and applicable for the respective learners around their whole life time. Top most advantages can be categorized as adapting and coping with modern rapid changing world, higher remuneration for white color jobs and most importantly self-content for high quality physical life and virtual thought. LLL has always been a good strategy to make opportunity for deserving people to practice it whole life and take maximum benefit out of it. UMP is pursuing to know their position about lifelong learning perspective to find out their optimum course of action. This study was conceived to analyze lifelong learning scenario in UMP. It used a descriptive analysis together with multiple regression from primary data with structured questionnaire. The study found that almost all the learners were quite satisfied for the services they received in their life time. Maximum variables except a few asked to the beneficiaries of UMP have positive contribution to overall impact and feedback of LLL graduate marketability. The study suggested some measures with emphasize for specific subject and certificate program for the prospective beneficiaries.